(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
The soil rhizosphere community is an important indicator of the overall health of the plant, and the resulting yield at harvest. The study determined the rhizosphere microbial community structure of transgenic and non-transgenic maize plants. A farm plot was divided into 4 sections for transgenic maize (SAMMAZ 74T) and non-transgenic variety 8325-8. The maize was infected at the tasseling stage and phenolic content determined after 10 days. The microbial community indices were subsequently determined using metagenomic tools. The physicochemical parameters and microbial population of the soil for maize 8325-8 and SAMMAZ 74T were not significantly differently at P<0.05. The soil with infected maize were the most diverse with Shannon index 1.834. The soil with infected maize were the most diverse with Shannon index 1.834. The transgenic maize SAMMAZ 74T had the highest dominance of bacteria (0.2536) and fungi (0.10930). Proteobacteria was the predominant bacteria phylum while Ascomycota was the predominant fungal phylum. The study concludes that the non-transgenic maize had better contribution to the soil microbial community than the transgenic maize variety.